Analysis Identifying Marxian Political Economy in Indonesia - Prasya, Sakti Dwiantoro; Saepudin, Eli Apud; Zahro, Siti Aminatul; Wulandari, Meylani; Ramadhan, Muhammad Rihal; Aghnia, Zulfan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Marxian political economy has been one of the theories that has influenced economic and political thought in various countries, including Indonesia. This theory puts forward a critical view of capitalism and the relationship between social classes. In the Indonesian context, Marxian political economy analysis can provide deep insights into the existing economic structure, wealth distribution and social inequality. The main objective of Marxian analysis is to expose the structures and mechanisms that underlie injustice and inequality in society. In understanding Indonesia's economic dynamics through the theoretical framework of Marxian political economy, there are problems that become the main focus. One of the most dominant problems is related to the high income gap between community groups and the wide infrastructure gap between regions in Indonesia. This research is expected to provide deeper insights into the interaction between economic and political structures, and its implications for social development in Indonesia.